Abordaje interhemisférico contralateral. Nota técnica - Jaikin, Mario (Revista Argentina de Neurocirugía, 2021)
Contralateral transcallosal  approach is a variant of the well-know interhemispheric transcallosal approach that allows to optimize the lateral wall ventricles lesions management. Neuronavigation planning allows us to deal with a  caudate nucleus cavernoma contiguous to internal capsule without callosotomy and additional damage neither.